Dying with a Left Ventricular Assist Device as Destination Therapy - Dunlay, Shannon M. (Circ Heart Fail, 2016)
BACKGROUND: Despite the ability of left ventricular assist device as destination therapy (DT-LVAD) to prolong survival for many patients with advanced heart failure (HF), little is known about the eventual end-of-life care that patients with DT-LVAD receive. METHODS AND RESULTS: All patients undergoing DT-LVAD at the Mayo Clinic in Rochester, Minnesota from January 1, 2007 through September 30, 2014 who subsequently died prior to July 1, 2015 were included. Information about end-of-life care was obtained from documentation in the electronic medical record. Of 89 patients that died with a DT-LVAD, the median (25(th)–75(th) percentile) time from LVAD implantation to death was 14 (4–31) months. The most common causes of death were multiorgan failure (26%), hemorrhagic stroke (24%), and progressive HF (21%). Nearly half (46%) of patients saw palliative care within one month prior to death; however, only 13 (15%) patients enrolled in hospice a median 11 (range 1–315) days prior to death. Most patients (78%) died in the hospital, of which 88% died in the intensive care unit. In total, 49 patients had their LVAD deactivated prior to death, with all but 3 undergoing deactivation in the hospital. Most patients died within an hour of LVAD deactivation, and all within 26 hours. CONCLUSIONS: In contrast to the general HF population, most patients with DT-LVAD die in the hospital and very few utilize hospice. Further work is needed to understand these differences and to determine whether patients with DT-LVAD are receiving optimal end-of-life care.